The relationship between oral health-related quality of life, the need for orthodontic treatment and bullying, among Brazilian teenagers - Gatto, Renata Colturato Joaquim; Garbin, Artênio José Ísper; Corrente, José Eduardo; Garbin, Cléa Adas Saliba (Dental Press International, 2019)
ABSTRACTIntroduction:Orthodontic treatment aims at oral health and restoration of function as main objectives, however, psychological and social effects end up being the main reason for the demand for treatment.Objective: To determine the association between the oral health-related quality of life (OHRQoL), the need for orthodontic treatment and bullying among Brazilian teenagers.Methods: This was a cross-sectional epidemiological study. To assess the malocclusion, the Dental Aesthetic Index was used. And the Oral Health Impact Profile-14 was used to analyze the OHRQoL. The Kidscape questionnaire was used to investigate cases of bullying. The following variables were also included: previous orthodontic treatment and a desire to fix the teeth to improve one’s appearance. Multivariate analysis was performed using logistic regression considering the poor OHRQoL as a response variable.Results: 815 teenagers participated in the study. There was a statistically significant association between oral health-related quality of life and the variables: previous orthodontic treatment (p= 0.0270), desire to fix the teeth (p< 0.0001), sex (p= 0.0309), history of being a victim of bullying (p< 0.0001), frequency of bullying episodes (p= 0.0170), and consequences of bullying (p< 0.0001). The following were considered as risk factors for poor OHRQoL: lack of previous orthodontic treatment (OR = 2.191) and negative consequences of bullying (OR = 3.042).Conclusion: The need for orthodontic treatment was not associated with the OHRQoL; however, bullying and previous orthodontic treatment had a statistically significant association with this variable.

RESUMOIntrodução:o tratamento ortodôntico visa à saúde bucal e ao reestabelecimento da função como objetivo final; no entanto, os efeitos psicológicos e sociais acabam sendo o principal motivo da procura pelo tratamento.Objetivo: determinar a associação entre a qualidade de vida relacionada à saúde bucal (QVRSB), a necessidade de tratamento ortodôntico e o bullying entre os adolescentes.Métodos: trata-se de um estudo epidemiológico transversal. Para avaliar a má oclusão, foi utilizado o Dental Aesthetic Index. O instrumento Oral Health Impact Profile-14 foi utilizado para analisar a QVRSB. O questionário Kidscape foi utilizado para verificar os casos de bullying. Também foram incluídas as variáveis: tratamento ortodôntico prévio e desejo de corrigir os dentes para melhorar a aparência. A análise multivariada foi realizada por meio de regressão logística, considerando-se a qualidade de vida ruim como variável resposta.Resultados:815 adolescentes participaram da pesquisa. Houve associação, estatisticamente significativa, entre a qualidade de vida relacionada à saúde bucal e as variáveis: tratamento ortodôntico prévio (p= 0,0270), desejo de corrigir os dentes (p< 0,0001), sexo (p= 0,0309), bullying (p< 0,0001), frequência de episódios de bullying (p= 0,0170) e consequências do bullying (p< 0,0001). Foram considerados como fatores de risco para uma QVRSB ruim os adolescentes que não realizaram tratamento ortodôntico prévio a esse estudo (OR= 2,191) e aqueles que revelaram consequências negativas relacionadas aos episódios de bullying (OR= 3,042).Conclusão: a necessidade de tratamento ortodôntico não foi associada à qualidade de vida relacionada à saúde bucal, já o bullying e o tratamento ortodôntico prévio tiveram associação estatisticamente significativa com essa variável.
Keywords: Adolescent; Quality of life; Bullying; Orthodontics; Malocclusion; Adolescente; Qualidade de vida; Bullying; Ortodontia; Má oclusão